Democratic Republic of the Congo : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with the Democratic Republic of the Congo (DRC) highlights that real gross domestic growth reached 5.8 percent in 2018, buoyed by stronger copper and cobalt prices and increased production. The main risks include an escalation of the Ebola epidemic; fiscal loosening leading to monetization of budget deficits; a relapse in copper and cobalt prices; an intensification of ongoing armed conflicts; and resistance to reform from vested interests. Transparency and accountability in the management of natural resources are major challenges facing DRC. It is recommended to step-up revenue mobilization, notably by simplifying taxes and integrating mining revenue into the central government Treasury. It is also important to enhance transparency, including through public tendering for the sale of mining assets, publication of audited financial statements of state-owned enterprises, and greater monitoring of public assets.